BODY IMAGE AND SELF-ESTEEM AMONG FEMALE STUDENTS IN PSYCHOLOGY DEPARTMENT - Manoe, Rizkita Fadillah Angel; Adu, Apris A.; Damayanti, Yeni; Junias, Marylin Susanti (Journal of Health and Behavioral Science, 2025)
Adolescence is a period when individuals begin to pay more attention to their physical condition, which is known as body image. Body image is defined as an individual's perception of how satisfied and accepting they are of their physical appearance, which is influenced by their own perceptions. Self-esteem is the result of an individual's evaluation of themselves, expressed in their attitudes and acceptance of their qualities. This study aims to determine whether there is a relationship between body image and self-esteem among female psychology students at Nusa Cendana University, involving 156 female participants. This study employed a quantitative research method through the distribution of questionnaires. The hypothesis test found a significance value of 0.006 < 0.05, which means that the study indicates a relationship between body image and self-esteem among female students. Students with a better perception of their body image tend to show positive emotional responses, including self-esteem.